2015
DOI: 10.1016/j.bbr.2015.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age on cognitive control during semantic categorization

Abstract: We used event-related potentials (ERPs) to study age effects of perceptual (basic-level) vs. perceptual-semantic (superordinate-level) categorization on cognitive control using the go/nogo paradigm. Twenty-two younger (11 M; 21±2.2 years) and 22 older adults (9 M; 63±5.8 years) completed two visual go/nogo tasks. In the single car task (SiC) (basic), go/nogo responses were made based on single exemplars of a car (go) and a dog (nogo). In the object animal task (ObA) (superordinate), responses were based on mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 78 publications
(127 reference statements)
14
35
1
Order By: Relevance
“…Thus, as opposed to solely focusing on working memory, the test engages the retina, the visual cortex and the motor cortex, all of them are shown to be affected pre-dementia or in early stages of the disease [21][22][23][24][25][26][27][28] . The ICA's focus on speed and accuracy of processing visual information [29][30][31][32] is in line with latest evidence suggesting that simultaneous object perception deficits are related to reduced visual processing speed in amnestic mild cognitive impairment 33 . Additionally, the proposed test is self-administered and is intrinsically independent of language and culture, thus making it ideal for large-scale pro-active cognitive screening and cognitive monitoring.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Thus, as opposed to solely focusing on working memory, the test engages the retina, the visual cortex and the motor cortex, all of them are shown to be affected pre-dementia or in early stages of the disease [21][22][23][24][25][26][27][28] . The ICA's focus on speed and accuracy of processing visual information [29][30][31][32] is in line with latest evidence suggesting that simultaneous object perception deficits are related to reduced visual processing speed in amnestic mild cognitive impairment 33 . Additionally, the proposed test is self-administered and is intrinsically independent of language and culture, thus making it ideal for large-scale pro-active cognitive screening and cognitive monitoring.…”
Section: Introductionsupporting
confidence: 57%
“…Particularly, in early stages of the disease, brain areas associated with the visuo-motor pathway are affected, beginning with the retina [22][23][24]27 , the visual cortex 21,26,27 and the motor cortex 25,28 , so together these represent more effective areas to look for the impact of early stage neurodegeneration as opposed to solely focusing on memory. The ICA focuses on cognitive functions such as speed and accuracy of processing visual information which have been shown to engage a large volume of cortex, while being a predictor of people's cognitive performance [30][31][32] ; thus, monitoring the performance and functionality of these areas altogether can be a reliable early indicator of the disease onset.…”
Section: Potential Use Of Ica For Early Detection Of Dementiamentioning
confidence: 99%
“…Basic and superordinate categorizations are more frequently involved in day-to-day functioning than subordinate categorization, which involves more in-depth/expert knowledge (e.g., knowledge used by dog experts, car experts, bird experts). Previously, we examined the effects of age on cognitive control using Go/NoGo tasks involving basic and superordinate categorization in an EEG study by comparing cognitively normal young and older adults [47]. We found that cognitively normal older adults had reduced NoGo-N2 and NoGo-P3 amplitudes compared to younger adults, suggesting alterations in neural processing during response inhibition.…”
Section: Introductionmentioning
confidence: 88%
“…Many EEG-based studies of normally aging individuals have used the Go/NoGo paradigm to study response inhibition [45][46][47][48][49][50]. The standard Go/NoGo task requires subjects to respond to a certain type of stimuli (Go) and inhibit/refrain from responding to another type of stimuli (NoGo), pre-defined by a specific set of rules.…”
Section: Introductionmentioning
confidence: 99%
“…These Go/NoGo studies typically show changes in the N2 and P3 ERP components in normal cognitive aging (e.g., Pfefferbaum et al, 1985; Eimer, 1993; Falkenstein et al, 1999; Mudar et al, 2015; Barry et al, 2016; Kropotov et al, 2016). Only a couple of studies have examined whether aMCI affects ERPs corresponding to Go/NoGo tasks relative to normal cognitive aging (Cid-Fernandez et al, 2014; Mudar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%